3D Printing of Graphene Aerogels. Issue 13 (10th February 2016) - Zhang, Qiangqiang; Zhang, Feng; Medarametla, Sai Pradeep; Li, Hui; Zhou, Chi; Lin, Dong
Abstract : 3D printing of a graphene aerogel with true 3D overhang structures is highlighted. The aerogel is fabricated by combining drop‐on‐demand 3D printing and freeze casting. The water‐based GO ink is ejected and freeze‐cast into designed 3D structures. The lightweight (<10 mg cm −3 ) 3D printed graphene aerogel presents superelastic and high electrical conduction.